2007
DOI: 10.1007/s11709-007-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of a long span suspension bridge and running safety of a train under wind action

Abstract: When trains run over the bridge, the deflection and vibration of the bridge may be further exaggerated. The large deflection and vibration of the bridge may in turn affect the safe running of trains and the riding comfort of the passengers.Little information is publicly available on this subject. Most researches focus on either the wind effects on long suspension bridges without considering running trains [2−4] or the dynamic interaction between the bridge and the trains excluding wind actions [5−8]. By taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…• Recently a number of authors have reported on the effect of cross winds on trains on long span bridges where coupled calculations have been carried out considering bridge and train aerodynamics and dynamics, and the coupling of these different effects, in order to understand the effect of trains on bridge stability in cross winds, and bridge movement on the stability of trains in cross winds (85,86) .…”
Section: Other Issuesmentioning
confidence: 99%
“…• Recently a number of authors have reported on the effect of cross winds on trains on long span bridges where coupled calculations have been carried out considering bridge and train aerodynamics and dynamics, and the coupling of these different effects, in order to understand the effect of trains on bridge stability in cross winds, and bridge movement on the stability of trains in cross winds (85,86) .…”
Section: Other Issuesmentioning
confidence: 99%
“…The model was validated by comparing it with measurements of the first 18 modal frequencies and shapes of the actual bridge. Using this model, Guo et al [ 21 ] predicted the dynamic displacement and acceleration responses of coupled train and bridge systems in crosswinds. However, they modeled the bridge deck as a simplified spine beam of equivalent sectional properties and were thus unable to capture the local stress and strain behavior of the bridge.…”
Section: Numerical Simulation: Dynamic Responses Of Long-span Multmentioning
confidence: 99%
“…The influence of crosswinds on a moving vehicle deserves constant attention. Severe wind disasters may influence the moving-speed limit of a vehicle, affect its transportation capacity, and even cause vehicle shutdown or accidents [1][2][3][4][5]. For example, China is one of the few countries in the world that is prone to severe wind disasters.…”
Section: Introductionmentioning
confidence: 99%